PROSES PENGAMBILAN KEPUTUSAN WISATAWAN DALAM MENGUNJUNGI TAMAN AGROWISATA BUKIT NAANG KECAMATAN BANGKINANG SEBERANG KABUPATEN KAMPAR PROVINSI RIAU - Ade Ayu Pranita; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research and how much influence factors travelers decision beforevisiting the park agrotourism hill Bukit Naang Bangkinang Seberang DistrictKampar Regency Riau Province.The research use descriptive methode to analyze the problems. The sampelinside this research are 70 respondendence by using accidental sampling. And thetechnique to collected data in this research are using observation, quetionnaire,and interview. And it was using likert scale to know the lenght of intervals.Based on the research, the respon of respondence to decision making visitthe park agrotourism hill Bukit Naang, because factors excelllence tourist thathas the greatest score, are nature and type of attraction and the quality of service.Keywords : The decision making process travelers, Agrotourism, Outbond,Tourism